Informal versus Formal Search: Which Yields a Better Pay? - Semih Tumen (Institute for the Study of Labor (IZA), 2015)
Estimates on the effect of job contact method – i.e., informal versus formal search – on wage offers vary considerably across studies, with some of them finding a positive correlation between getting help from informal connections and obtaining high-paying jobs, while others finding a negative one. In this paper, I theoretically investigate the sources of discrepancies in these empirical results. Using a formal job search framework, I derive an equilibrium wage distribution which reveals that the informal search yields for some groups higher and for some others lower wages than formal search. The key result is the existence of nonmonotonicities in wage offers. Two potential sources of these nonmonotonicities exist: (i) peer effects and (ii) unobserved worker heterogeneity in terms of the inherent cost of maintaining connections within a productive informal network. The model predicts that a greater degree of unobserved heterogeneity tilts the estimates toward producing a positive correlation between informal search and higher wages, whereas stronger peer influences tend to yield a negative correlation. This conclusion informs the empirical research in the sense that identification of the true correlation between job contact methods and wage offers requires a careful assessment of the unobserved heterogeneity and peer influences in the relevant sample.
Keywords: D85; J31; J64; 330; heterogeneity; peer effects; informal networks; job search; nonmonotonicities